Investigations on a platinum catalyzed membrane for electrolysis step of copper‐chlorine thermochemical cycle for hydrogen production. (25th November 2020) - Banerjee, Atindra Mohan; Antony, Rajini P.; Pai, Mrinal R.; Kumar, Asheesh; Tripathi, Arvind K.
Summary: Considering the low temperature demand (~550°C maximum) and high efficiency (~43%), Cu–Cl thermochemical water splitting cycle has immense potential as a futuristic scalable hydrogen generation process. CuCl/HCl electrolysis is the crucial hydrogen generation step in the Cu–Cl thermochemical cycle. The efficiency of this electrolysis process is highly dependent on the performance of the membrane electrode assembly (MEA) employed. To explore the suitability of the platinized membrane for this step, in this study, we have investigated a Pt/Nafion‐117 MEA prepared by in‐situ impregnation‐reduction method for CuCl/HCl electrolysis. A single‐cell PEM‐type electrolyser (4 cm 2 active area) consisting of serpentine channels (2 cm × 2 cm) grooved in graphite flow field plates was designed and fabricated to carry out the CuCl/HCl electrolysis. Platinum electrocatalyst was deposited on Nafion‐117 membrane on the cathodic side by reduction of hexachloroplatinic acid (H2 PtCl6 ) with sodium borohydride (NaBH4 ) by the impregnation‐reduction method which served as the MEA. Monodispersed nanocrystalline Pt particles formed a ~30 μm thick electrocatalyst layer on the membrane. Pt/Nafion‐117 MEA was found to be effective for CuCl /HCl electrolysis. In a PEM‐type electrolyser with Ar‐purged 0.2 M CuCl in ~2 M HCl solution as anolyte flowing at ~ 8.8 mLmin −1, a current density of ~100 mA cm −2 was achieved at a cell voltage of 1 V. However, undesired Cu‐crossover could be noticed from anode to cathode side during operation. Abstract : Platinized membrane prepared by in‐situ impregnation‐reduction method by depositing Pt on Nafion‐117. Monodispersed nanocrystalline Pt‐particles formed a ~30 μm thick electrocatalyst layer on the Nafion‐117 membrane. A single cell PEM type electrolyser (4 cm 2 active area) was designed and fabricated with graphite flow field plates 100 mAcm −2 at a cell voltage of 1 V with 0.2 M CuCl in ~2 M HCl solution as anolyte Platinized membrane: An effective MEA for CuCl/HCl electrolysis